(3GdGYdGe GdeYGUQ hJbfjGJg GdMOjKIs - (3eLO gGTe(B, (3GdgGTejs ((3YeGf(B:s (3OGQ GdefGgL ddfTQ hGdJhRjY(B,s, 2006)
(3jVe GdEYdGe GdELJeGYj, GdEYdGe GdSjGSj, GdEYdGe GdOhdj hhSGFdg GdMOjKIs
(3HjHdjhZQGajG(B: (3U U(B.275-283s
Keywords: (3GdEYdGe (B- (3GdEYdGf s; (3GdEYdGe GdOhdjs